Agmatine relieves behavioral impairments in Fragile X mice model. (15th November 2022) - Jeon, Se Jin; Kwon, Huiyoung; Bae, Ho Jung; Gonzales, Edson Luck; Kim, Junhyeong; Chung, Hye Jin; Kim, Dong Hyun; Ryu, Jong Hoon; Shin, Chan Young
Abstract: Background: Fragile X syndrome (FXS) is the most common heritable form of neurodevelopmental disorder, which is caused by the loss of fragile X mental retardation protein (FMRP) expression. Despite the unceasing efforts to develop therapeutic agents against FXS based on the pathophysiological changes observed in animal models of FXS and human patients, therapeutic candidates including mGluR signaling modulators have failed to provide sufficient effects. Based on the recent successful demonstration of an endogenous polyamine, agmatine, to improve the autism-like symptoms in the valproic acid animal model of autism, we investigated the effects of agmatine against FXS symptoms using Fmr1 knockout (KO) mice. Methods: We used male Fmr1 KO mice for behavioral tests such as marble burying, open-field test, memory tasks, social interaction tests and startle response to confirm the symptoms of FXS. We also checked the electrophysiological profile of neural activity in agmatine-treated Fmr1 KO mice. Results: Agmatine reversed the compulsion, learning and memory deficits, hyperactivity, aberrant social interaction, and communication deficit in Fmr1 KO mice while it normalized the aberrant LTP and LTD in the hippocampus. Conclusions: The results highlight the potential of agmatine's novel disease-ameliorating effects in FXS, which warrants further studies to ascertain whether these findings translate into clinical effects in FXS patients. Highlights: Fragile X syndrome showed an exaggerated NMDA receptor signaling, problems in synaptic transmission, and abnormal behaviors. Agmatine is an endogenous polyamine and functions as a synaptic neurotransmitter. Agmatine reversed these problems in the model of fragile X syndrome mice.